Juvenile systemic lupus erythematosus presenting only as nonscarring alopecia - N M Vinitha; Reena Rai; G Uma Maheswari (Wolters Kluwer Medknow Publications, 2022)
Juvenile onset systemic lupus erythematosus (JSLE) is a rare multisystem, autoimmune disorder. Alopecia in SLE generally follows a pre-established disease with systemic symptoms. A 13-year-old girl presented with sudden hair loss over the vertex of scalp of 1-month duration. No other cutaneous or systemic symptoms were noted. Trichoscopy, histopathology, positive ANA, and low complement levels helped in diagnosing JSLE. Patchy nonscarring alopecia, as the sole presenting feature without systemic involvement, is rare.